A educação e o enfrentamento da violência sexual contra crianças e adolescentes: um balanço de dissertações e teses brasileiras no período de 2010 a 2020 - Lamazon, Vanessa Lima (2021)
Violence against children and adolescents is not a recent fact, nor its discussed at school. Studies indicate weaknesses related to the initial and continuing education of school professionals with regard to situations of coping with sexual violence (identification, approach and referral of cases). This research carried out had as general objective to investigate Brazilian studies that indicate the participation of school units in the identification and referrals in cases of sexual violence against children and adolescents between 2010 and 2020. The survey of theses and dissertations was carried out in the archives of the Brazilian Digital Library of Theses and Dissertations. The research identified 18 studies, being 5 theses and 13 dissertations, works with specific objectives that sought to apprehend the socioeconomic characteristics of gender, race and ethnicity of the victims and the participation of the school in this context. This is a research with a qualitative approach, bibliographical in nature, with content analysis being carried out in its reading, categorization and inference construction phases. The descriptors researched were: “sexual violence against children and adolescents; school”, seeking to answer the following question: What is the school's participation in the process of identifying and referring cases of violence against children and adolescents?”. It was considered the hypothesis that school professionals, who would be in daily contact with the victims, could identify the perpetrated violence more quickly than other protection bodies, since children and adolescents spend a large part of their time in the school, after the family environment. The results showed that most of the violated subjects are of compulsory school age and suffer intra-family violence. It was found that violence against children and adolescents has been perceived at school, but there is underreporting by its agents due to the difficulties encountered in relation to approaching and referring cases, whether due to the lack of training for coping and/or fear of reprisals. The results also suggested the need for training of school professionals and coordination so that the school understands its role in the network of coping and protection of children and adolescents, strengthening the fight against violence suffered by its target audience, since the subjects most violated are girls and that school, after the family, is the main place of socialization and interaction, being a favorable space to identify the consequences of this trauma.